Marketing: a new organising principle for local government - May, John; Newman, Karin (1999)
A local government practitioner and a marketing academic consider the claims for marketing as a new organising principle for local government. They scrutinise the most frequent objections to the concept of marketing in this context and demonstrate that these have little or no force. This is especially true concerning the emerging paradigms of relationship marketing and Webster's development of the marketing concept. The authors conclude that a marketing philosophy underlies much of the new approach to local government service provision, and set out some of the characteristics which local government marketing needs to have. - Reproduced
Keywords: Marketing; Local government